SKEW PERMUTATION CODES OVER Ak - Yanuarsih, Susi
This thesis discusses the ring Ak constructed by using polinomial ring over F2 with k variables modulo the ideal hv2 i ???? vi; vivj ???? vjvii. We also dene codes over ring Ak, start with two kinds of Gray maps which will be used for characterization of skew cyclic codes over Ak. That characterization will be used for construction of skew cyclic codes over Ak. Then, this thesis also discusses about a skew permutation code over Ak and its basic properties, followed by a monomial code with its properties which are used to determine parity check matrix for skew cyclic permutation codes over Ak.